Laser Displacement Sensors for Wind Tunnel Model Position Measurements - Matthew Kuester; Nanyaporn Intaratep; Aurélien Borgoltz (Sensors, 2018)
Wind tunnel measurements of two-dimensional wing sections, or airfoils, are the building block of aerodynamic predictions for many aerodynamic applications. In these experiments, the forces and pitching moment on the airfoil are measured as a function of the orientation of the airfoil relative to the incoming airflow. Small changes in this angle (called the angle of attack, or <semantics> α </semantics> ) can create significant changes in the forces and moments, so accurately measuring the angle of attack is critical in these experiments. This work describes the implementation of laser displacement sensors in a wind tunnel; the sensors measured the distance between the wind tunnel walls and the airfoil, which was then used to calculate the model position. The uncertainty in the measured laser distances, based on the sensor resolution and temperature drift, is comparable to the uncertainty in traditional linear encoder measurements. Distances from multiple sensors showed small, but statistically significant, amounts of model deflection and rotation that would otherwise not have been detected, allowing for an improved angle of attack measurement.